Chronic Intermittent Hypobaric Hypoxia Enhances Bone Fracture Healing - Zhang, Li; Jin, Lin; Guo, Jialiang; Bao, Kai; Hu, Jinglue; Zhang, Yingze; Hou, Zhiyong; Zhang, Liping (Frontiers in Endocrinology, 2021)
The effect of chronic intermittent hypobaric hypoxia (CIHH) on bone fracture healing is not elucidated. The present study aimed to investigate the role of CIHH on bone fracture healing and the mechanism. The Sprague-Dawley rats were randomly divided into the CIHH group and control group and monitored for 2, 4, or 8 weeks after femoral fracture surgery. Bone healing efficiency was significantly increased in the CIHH group as evidenced by higher high-density bone volume fractions, higher bone mineral density, higher maximum force and higher stiffness. Histologically, the CIHH group exhibited superior bone formation, endochondral ossification, and angiogenic ability compared with the control group. The expression of HIF-1α and its downstream signaling proteins: VEGF, SDF-1/CXCR4 axis were increased by the CIHH treatment. Moreover, the expression of RUNX2, osterix, and type I collagen in the callus tissues were also up-regulated in the CIHH group. In conclusion, our study demonstrated that CIHH treatment improves fracture healing, increases bone mineral density, and bone strength, via the activation of HIF-1α and bone production-related genes.